Malaysia’s Post-9/11 Security Strategy: Winning "Hearts and Minds" or Legitimising the Political Status Quo? - Andrew Humphreys (Kajian Malaysia, 2010)
Since the Emergency, the Malaysian government has maintained a security policy which somewhat paradoxically combines the use of coercive, repressive legislation with a "hearts and minds" ideology. Following 9/11, I argue that the government has adapted this "hearts and minds" approach to the so-called War on Terror. The Barisan Nasional governments of Mahathir Mohamad and Abdullah Badawi both formulated ideological strategies designed to undermine the ideological strength of al-Qaeda and establish Malaysia as a leader of the Muslim world. Mahathir and Abdullah hinged their ideological approach on a state-constructed form of Islam and sought to portray Malaysia as a tolerant and moderate Muslim country. However, it will be shown that the use of ideology in Malaysia is often calibrated to ensure regime security rather than national security. The Malaysian government has used its ideology to promote elite interests and limit the discursive space for alternative and opposing viewpoints. Significantly, ideology has been used to justify crackdowns against genuine political opponents and to legitimise the political status quo.